Financial Sector Reforms and the Role of Central Bank in India: A Post-Global Financial Crisis Perspective - Bala, Tarun; Singh, Devender (Indian Journal of Finance, 2012)
Indian Financial institutions have largely escaped the effects of the unfettered operation of financial markets. The present analysis arises in the wake of the recent global financial crisis and apprehensions for the need of policy reforms in the financial sector. The R.H. Patil Committee, the Tarapore II Committee, the Percy Mistry Committee and the Raghuram Rajan Committee reports were drafted and submitted when the recent global crisis had not unfolded. These Committee reports evoked considerable debate. However, India managed to escape with relatively small damage from the severe impact of the two financial crisis (South East Asian financial crisis of 1997 and the sub-prime crisis of 2007) in comparison to the rest of the world. Financial sector reforms earlier meant for deregulation, but now, it means regulation and improving the quality as well as effectiveness of the economy. The domain of analysis of this paper is somewhat limited. This paper doesn't analyze all the four committee reports on financial sector reforms.